GAMMA-RAY LINEAR-POLARIZATION MEASUREMENT ON ORIENTED NUCLEI - Rikovska, J; Stone, N; Green, V (Baltzer Science Publishers, Baarn/Kluwer Academic Publishers, 1985)
Measurement of linear polarization of gamma-rays from nuclei oriented by hyperfine interaction at low temperatures using the3He/4He dilution refrigerator at the SERC Daresbury Laboratory is reported. Three different types of a Compton polarimeter were assembled using coaxial Ge(Li) detectors. The method was applied to192Ir Fe and60Co Fe and a polarization detection efficiency curve and a figure of merit for each polarimeter were produced. As a result of combined directional distribution and linear polarization measurements multipole mixing ratios of several transitions in192Pt have been obtained and are compared with theoretical predictions. © 1985 J.C. Baltzer A.G., Scientific Publishing Company.